Comprehensive genomic identification of cotton starch synthase genes reveals that GhSS9 regulates drought tolerance - Dai, Maohua; Yang, Xiaomin; Chen, Quanjia; Bai, Zhigang (Frontiers in Plant Science, 2023)
Introduction Starch metabolism is involved in the stress response. Starch synthase (SS) is the key enzyme in plant starch synthesis, which plays an indispensable role in the conversion of pyrophosphoric acid to starch. However, the SS gene family in cotton has not been comprehensively identified and systematically analyzed. Result In our study, a total of 76 SS genes were identified from four cotton genomes and divided into five subfamilies through phylogenetic analysis. Genetic structure analysis proved that SS genes from the same subfamily had similar genetic structure and conserved sequences. A cis-element analysis of the SS gene promoter showed that it mainly contains light response elements, plant hormone response elements, and abiotic stress elements, which indicated that the SS gene played key roles not only in starch synthesis but also in abiotic stress response. Furthermore, we also conducted a gene interaction network for SS proteins. Silencing GhSS9 expression decreased the resistance of cotton to drought stress. These findings suggested that SS genes could be related to drought stress in cotton, which provided theoretical support for further research on the regulation mechanism of SS genes on abiotic starch synthesis and sugar levels.